Not a benign motor neuron disease: longitudinal imaging captures relentless motor connectome disintegration in primary lateral sclerosis. (1st March 2023) - Tahedl, Marlene; Tan, Ee Ling; Shing, Stacey Li Hi; Chipika, Rangariroyashe H.; Siah, We Fong; Hengeveld, Jennifer C.; Doherty, Mark A.; McLaughlin, Russell L.; Hardiman, Orla; Finegan, Eoin; Bede, Peter
Abstract: Background and purpose: Primary lateral sclerosis (PLS) is a progressive upper motor neuron disorder associated with considerable clinical disability. Symptoms are typically exclusively linked to primary motor cortex degeneration and the contribution of pre‐motor, supplementary motor, cortico‐medullary and inter‐hemispheric connectivity alterations are less well characterized. Methods: In a single‐centre, prospective, longitudinal neuroimaging study 41 patients with PLS were investigated. Patients underwent standardized neuroimaging, genetic profiling with whole exome sequencing, and comprehensive clinical assessments including upper motor neuron scores, tapping rates, mirror movements, spasticity assessment, cognitive screening and evaluation for pseudobulbar affect. Longitudinal neuroimaging data from 108 healthy controls were used for image interpretation. A standardized imaging protocol was implemented including 3D T1‐weighted structural, diffusion tensor imaging and resting‐state functional magnetic resonance imaging. Following somatotopic segmentation, cortical thickness analyses, probabilistic tractography, blood oxygenation level dependent signal analyses and brainstem volumetry were conducted to evaluate cortical, brainstem, cortico‐medullary and inter‐hemispheric connectivity alterations both cross‐sectionally and longitudinally. Results: Our data confirm progressive primary motor cortex degeneration, considerable supplementary motor and pre‐motor area involvement, progressive brainstem atrophy, cortico‐medullary and inter‐hemispheric disconnection, and close associations between clinical upper motor neuron scores and somatotopic connectivity indices in PLS. Discussion: Primary lateral sclerosis is associated with relentlessly progressive motor connectome degeneration. Clinical disability in PLS is likely to stem from a combination of intra‐ and inter‐hemispheric connectivity decline and primary, pre‐ and supplementary motor cortex degeneration. Simple 'bedside' clinical tools, such as tapping rates, are excellent proxies of the integrity of the relevant fibres of the contralateral corticospinal tract.